Venous thromboembolism prophylaxis in plastic surgery: a survey of the practice in Denmark. Issue 2 (4th March 2017) - Nielsen, Lea Juul; Matzen, Steen H.
Abstract: Background: Venous thromboembolism is a well-documented complication of surgery, including plastic surgery. However, few consensus guidelines on thromboembolism prophylaxis exist in plastic surgery and, thus, the different approaches in the public as well as the private clinics in Denmark were investigated using a web-based survey. Methods: Forty-two clinics were contacted and 45% responded. Results: The collected data reveals a lack of consensus in plastic surgery in Denmark, not only regarding the use of mechanical and chemical prophylaxis, but also which type of prophylaxis to apply, the duration of prophylaxis, and how to risk stratify the patients. Conclusion: The development of a guideline, based on plastic surgical data, using a validated risk assessment model, which combines the surgical risk with the patient related risk and recommends guidelines for mechanical as well as chemoprophylaxis is advised.